How and when frontline employees' environmental values influence their green creativity? Examining the role of perceived work meaningfulness and green HRM practices. (10th August 2021) - Al-Hawari, Mohd Ahmad; Quratulain, Samina; Melhem, Shaker Bani
Abstract: Drawing on the supply-value-fit and value-belief-norm theories, this study examines the effect of frontline employees' environmental values on their green creativity, identifying work meaningfulness as a mediating mechanism and green HR practices as a moderator. The hypothesized relationships are assessed using a multi-source survey of hotel employees (201 frontline employees and 96 managers) and multi-level analysis was used to test the hypotheses. Our findings suggest that frontline employees' environmental values affect their meaningfulness perceptions and green creativity differently depending on their organization's adoption of green HR practices. Specifically, our moderated mediation model delineates that environmental values indirectly affect green creativity through the intervening mechanism of perceived meaningfulness when management adopts green HR practices. These findings highlight the importance of the alignment of employee values and management practices in effecting positive employee behavior (green creativity). The theoretical and practical implications of these findings are discussed.